Legal aspects of business development and innovation in Poland - Dariusz Grzegorz Żak (Journal of Agribusiness and Rural Development, 2013)
At the beginning of this article the basic concepts related to the topic issues are presented. The article focuses on the rationale and ideas of creating entrepreneurship and innovation. On the one hand the work’s aim is to show the basic legal instruments which allow to conduct business in Poland, and to demonstrate the role of state bodies in the promotion of entrepreneurship. However, on the other hand the aim of this work is to show the legal instruments connected with competition and encourage entrepreneurs’ innovativeness, taking into account the current needs and trends occurring on the market.